"Collinsella bouchesdurhonensis" sp. nov., identified in human stool sample. (May 2017) - Bilen, M.; Cadoret, F.; Daoud, Z.; Fournier, P.-E.; Raoult, D.
Abstract: We report the main characteristics of "Collinsella bouchesdurhonensis" strain Marseille-P3296, which was isolated from a stool sample of a healthy 50-year-old pygmy (Baka) woman.